The Development of English Speaking Instructional Model for Students of Tapee University - Intaranak, Duangta; Chaturanon, Wimonrat (Ratchaphruek Journal, 2015)
The purposes of this study were; 1) to develop an instructional model of English speaking for the students of Tapee University, and 2) to study effects of the developed instructional model. The population used in this study were 145 first year undergraduate students of Tapee University and the samples were 66 first year students selected with purposive samplings technique. They were randomly assigned to an experimental and control groups of 32 and 34 persons, respectively. The research instruments were; 1) instructional model of English speaking for the students, 2) learning management plan, 3) the test of English speaking skill, and 4) the attitude inventory towards the instructional model. The statistics used for data analysis were; mean, standard deviation, analysis of covariance (ANCOVA), and t-test. The findings of this study were as follows: 1. The instructional model consisted of five components; 1) principles, 2) objectives, 3) the instructional process, 4) contents, and 5) measurement and evaluation. It was evaluated by experts and found to be highest appropriate instructional ( = 4.77, S.D. = 0.41). 2. The comparison of learning outcome was revealed that; 2.1 The English speaking skill of the experimental group learning through the developed instructional model was significantly higher than that control group at the .01 level. 2.2 The attitudes toward the instructional model of the experimental group was at high level ( = 3.67, S.D. = 1.09) which was higher than the set 3.50 criterion.